1995
DOI: 10.1007/bf00210426
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of ten exons of the CFTR gene in Greek cystic fibrosis patients: characterization of 74.5% of CF alleles including one novel mutation

Abstract: To initiate the complete characterization of mutations in the CFTR gene in Greek cystic fibrosis (CF) patients, we screened 184 patients for six relatively common mutations (delta F 508, G542X, G551D, 621 + 1 G-->T, N1303K, W1282X) using allele-specific hybridization and, in addition, analyzed exons 4, 5, 7, 8, 10, 11, 17b, 19, 20 and 21 using the method of denaturing gradient gel electrophoresis (DGGE). Six mutations accounted for 65.9% of the CF alleles in Greek patients, of which the delta F 508 mutation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

1996
1996
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
1
14
0
5
Order By: Relevance
“…Mutation frequencies used for population comparisons were derived from the compendium gathered by The Cystic Fibrosis Genetic Analysis Consortium (TCFGAC) (1994), supplemented with data for Greece by Kanavakis et al (1995). Only samples larger than 50 CF chromosomes were used, pooled by country independently for every mutation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutation frequencies used for population comparisons were derived from the compendium gathered by The Cystic Fibrosis Genetic Analysis Consortium (TCFGAC) (1994), supplemented with data for Greece by Kanavakis et al (1995). Only samples larger than 50 CF chromosomes were used, pooled by country independently for every mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, N1303K, G542X, R347P and 3849 + 10 kb C→T belong to the group of CF defects which are relatively common in other populations (TCFGAC 1994). A comparison of the frequency of these mutations in Bulgaria and in other European as well as Middle Eastern populations (TCFGAC 1994;Kanavakis et al 1995) is shown in Table 4. The frequency of N1303K in Bulgarians was relatively high (6.73%), the highest value reported for a European population.…”
Section: ∆F508mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, heterogeneity for CF mutations increases in the north-south and west-east direction, along with a decrease in the frequency of the dF508 mutation. The Mediterranean area has the highest CFTR heterogeneity, making genetic diagnosis by mutation analysis difficult Claustres et al, 1993;Chillon et al, 1994a,b;Chevalier-Porst et al, 1994;Savov et al, 1994;Bonizzato et al, 1995;Kanavakis et al, 1995).…”
Section: Introductionmentioning
confidence: 98%